1997
DOI: 10.1128/aac.41.11.2339
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary animal pharmacokinetics of the parenteral antifungal agent MK-0991 (L-743,872)

Abstract: MK-0991 (L-743,872) is a potent antifungal agent featuring long half-life pharmacokinetics. The pharmacokinetics of MK-0991 administered intravenously to mice, rats, rhesus monkeys, and chimpanzees is presented. Unique to MK-0991 is its consistent cross-species performance. The range of values for the pharmacokinetic parameters were as follows: clearance, 0.26 to 0.51 ml/min/kg; half-life, 5.2 to 7.6 h; and distributive volume, 0.11 to 0.27 liters/kg. The level of protein binding of MK-0991 was determined to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(68 citation statements)
references
References 21 publications
0
68
0
Order By: Relevance
“…6 and 9 mg/L in the murine liver when the standard 1 mg/kg dose was given, however, the drug levels produced by slightly supratherapeutic doses are unknown (Hajdu et al, 1997). Viewing the available earlier results in the light of the present findings draws the attention to the necessity of further investigations, including determination of serum drug levels produced by supratherapeutic echinocandin doses.…”
Section: Discussionmentioning
confidence: 81%
“…6 and 9 mg/L in the murine liver when the standard 1 mg/kg dose was given, however, the drug levels produced by slightly supratherapeutic doses are unknown (Hajdu et al, 1997). Viewing the available earlier results in the light of the present findings draws the attention to the necessity of further investigations, including determination of serum drug levels produced by supratherapeutic echinocandin doses.…”
Section: Discussionmentioning
confidence: 81%
“…The finding of relatively high MFCs for these less-susceptible yeast isolates may be overcome by some measure of dose scaling. Studies conducted in primates showed that the serum levels of MK-0991 administered at 0.5 mg/kg were above the 1 mg/l for up to 10 h [15]. In addition, in some mice tissues, such as liver, kidney, and the large intestine, drug concentrations were found to be severalfold higher than the serum levels [15].…”
Section: Mk-0991 and Fluconazole Mics Formentioning
confidence: 99%
“…Studies conducted in primates showed that the serum levels of MK-0991 administered at 0.5 mg/kg were above the 1 mg/l for up to 10 h [15]. In addition, in some mice tissues, such as liver, kidney, and the large intestine, drug concentrations were found to be severalfold higher than the serum levels [15]. Interestingly, MK-0991 MICs and MFCs for the majority of the strains tested in this study were lower than serum and tissue drug levels described in animal studies.…”
Section: Mk-0991 and Fluconazole Mics Formentioning
confidence: 99%
“…Anidulafungin is unique in that the drug undergoes slow chemical degradation independent of the liver to an open ring structure lacking antifungal activity [33]. Echinocandins widely distribute into tissues after intravenous administration, with the highest concentrations found in the liver, kidneys, large intestine, gall bladder, lung, and spleen [33,34]. Unlike the newer triazoles, all three echinocandins exhibit doseproportional linear pharmacokinetics with relatively low inter-and intra-patient variability.…”
Section: Pharmacokinetic Considerations With Echinocandinsmentioning
confidence: 97%